Propuesta para el diseño de la documentación del Sistema de Gestión de Calidad basado en la norma NTC ISO 9001:2015 para la Empresa Textiles y Creaciones el Universo (2021)
In this work, the results obtained from the design of the documentation made as a proposal for the company Textiles y Creaciones en Universo are delivered, with the objective that the company has a starting point in the implementation of the Quality Management System.